2014
DOI: 10.1124/jpet.114.213074
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transport of CCL11 across the Blood-Brain Barrier: Regional Variation and Importance of Blood Cells

Abstract: Increased blood levels of the eotaxin chemokine C-C motif ligand 11 (CCL11) in aging were recently shown to negatively regulate adult hippocampal neurogenesis. How circulating CCL11 could affect the central nervous system (CNS) is not clear, but one possibility is that it can cross the blood-brain barrier (BBB). Here, we show that CCL11 undergoes bidirectional transport across the BBB. Transport of CCL11 from blood into whole brain (influx) showed biphasic kinetics, with a slow phase preceding a rapid phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 42 publications
1
75
0
Order By: Relevance
“…Previous pre-clinical experiments have shown that circulating CCL11 is capable of crossing the blood brain barrier and results in decreased neurogenesis in mice [6,17]. In primary cell lines obtained from mice, treatment with exogenous CCL11 increases microglial migration and induces the production of microglial reactive oxygen species, directly contributing to neuronal death in co-culture systems [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous pre-clinical experiments have shown that circulating CCL11 is capable of crossing the blood brain barrier and results in decreased neurogenesis in mice [6,17]. In primary cell lines obtained from mice, treatment with exogenous CCL11 increases microglial migration and induces the production of microglial reactive oxygen species, directly contributing to neuronal death in co-culture systems [18].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation can induce CCL11 production in various cell types outside the CNS, such as leukocytes, fibroblasts, chondrocytes, and endothelial cells . A recent study described a system for rapid transport of CCL11 across the blood-brain barrier (Erickson et al, 2014), suggest-ing that blood-borne CCL11 may also affect microglia and accelerate the progression of various neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, eotaxin has been found to facilitate cognitive decline during aging by direct inhibition of adult hippocampal neurogenesis (Villeda et al, 2011). Interestingly, eotaxin undergoes a bidirectional transport through BBB that is mediated by binding to the blood cellular components in the slow phase and direct interactions with BBB in the rapid phase (Erickson et al, 2014). In the study by Goldsmith et al (2016a), higher levels of Monocyte Chemoattractant Protein-1 (MCP-1) were associated with worse performance in tests measuring processing speed, motor speed and lateralized coordination.…”
Section: Other Cytokinesmentioning
confidence: 99%